2012
DOI: 10.1007/978-3-642-34347-6_13
|View full text |Cite
|
Sign up to set email alerts
|

Requirements Sensemaking Using Concept Maps

Abstract: Abstract.Requirements play an important role in software engineering, but their perceived usefulness means that they often fail to be properly maintained. Traceability is often considered a means for motivating and maintaining requirements, but this is difficult without a better understanding of the requirements themselves. Sensemaking techniques help us get this understanding, but the representations necessary to support it are difficult to create, and scale poorly when dealing with medium to large scale prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Concept maps are used for different purposes however in another paper [30] concept maps are proposed for requirement validation also in which requirements are linked with source contents and rationales and both are represented by concept map. The assumption taken here is that analyst may find traces of requirements with its rationale and then validate the requirements.…”
Section: Research Question and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Concept maps are used for different purposes however in another paper [30] concept maps are proposed for requirement validation also in which requirements are linked with source contents and rationales and both are represented by concept map. The assumption taken here is that analyst may find traces of requirements with its rationale and then validate the requirements.…”
Section: Research Question and Methodologymentioning
confidence: 99%
“…Many tools are proposed for creating such visualized models [31]. However creating such associations and traces is problem of pre-requirement specification traceability pre-RST which is problematic area yet [10,30]. This paper only guides about usage of visualization model for, and emphasized its importance for validation purpose.…”
Section: Research Question and Methodologymentioning
confidence: 99%
“…The development team members carried out this activity during project meetings when all team members were present in the same location. The team members found the exercise so useful that, despite other commitments, they decided to hold a subsequent workshop three weeks later to consolidate the requirements concept maps for each area; the consolidated concept map is shown in Figure 4, and the process itself is described in more detail in [13].…”
Section: Sustaining Adoption Through Implementation Requires Creatmentioning
confidence: 99%
“…As the work described in [12], [13] shows in more detail, security and usability design problems often require creative solutions. This study has shown that integrating usability design practices into a project at an early stage, and sensitising team members to some of the techniques necessary to carry out this research, lays the groundwork for carrying out the research necessary for identifying the causes, rather than the symptoms, of design problems as and when they arise.…”
mentioning
confidence: 99%
“…6, the presentation of this application's navigation component can be optimized based on various parameters such as the device's operating system, input modalities screen size, screen orientation, etc. Taking these contextual characteristics into account is necessary in order to ensure the adaptive usability requirements of a multi-device ubiquitous application, but also, e.g., for meeting existing safety regulations regarding user distraction in-vehicle applications [16]. For such an in-vehicle infotainment (IVI) system, adaptation rules can be set to display the application's navigation bar fullscreen (see rule in Listing 1.2).…”
Section: Case Study: Adaptive Navigation Barmentioning
confidence: 99%